A, The The Influence of Digital Money and Digital Marketing on Consumer Shopping Decisions Through E-Commerce - alghifari, Adib Alghifari; Osly Usman (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Technological developments can change various sectors of life, one of which is the economic sector. Technological developments have given rise to new transaction tools, namely digital money, which itself can be used to replace currency which is already commonly circulating in society. Digital money itself is an electronic means of exchange that can be accepted as a legal and accepted means of payment or in short, digital money is money that has been digitized. Digital money itself means electronic money, digital transaction tools, digital currency, money stored in chips, and digitized rupiah. Technological developments also have an influence on advertising strategies where digital advertising or marketing is starting to emerge. The aim of the research is to measure the level of influence of digital money and digital marketing on shopping decisions via e-commerce, especially Tokopedia and Shopee. This research uses the SMART-PLS analysis method, using the Linkert measurement method for 100 respondents with a survey method using a questionnaire for data collection. From this research, the results show that there is a positive and significant influence for the digital money variable on shopping decisions, then there is a positive and significant influence for the digital marketing variable on shopping decisions, then there is a positive and significant influence for the variable shopping decisions via e-commerce . Furthermore, there is a negative and insignificant influence for the digital money variable on e-commerce, then there is a negative and insignificant influence for the digital marketing variable on e-commerce, then there is a negative and insignificant influence for the digital money variable on the decision to shop via e-commerce. -commerce, and finally there is a negative and insignificant influence for digital marketing variables on shopping decisions via e-commerce.